2014
DOI: 10.1007/s00394-014-0822-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-dose selenium on thyroid autoimmunity and thyroid function in UK pregnant women with mild-to-moderate iodine deficiency

Abstract: PurposeSelenium is an essential trace mineral and a component of selenoproteins that are involved in the production of thyroid hormones and in regulating the immune response. We aimed to explore the effect of low-dose selenium supplementation on thyroid peroxidase antibody (TPO-Ab) concentration and thyroid function in pregnant women from a mild-to-moderate iodine-deficient population.MethodsSamples and data were from a secondary analysis of Selenium in PRegnancy INTervention (SPRINT), a double-blind, randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 29 publications
3
67
0
8
Order By: Relevance
“…Effects were significant in our study already after 6 months intervention. Interestingly, our short-term findings are in accordance with a recent study, in which w6 months low-dose selenium supplementation decreased FT 4 and tended to decrease TSH, when compared with placebo (21). The comparability is however limited as study subjects were pregnant women and effects were seen only in thyroid antibody-positive individuals.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Effects were significant in our study already after 6 months intervention. Interestingly, our short-term findings are in accordance with a recent study, in which w6 months low-dose selenium supplementation decreased FT 4 and tended to decrease TSH, when compared with placebo (21). The comparability is however limited as study subjects were pregnant women and effects were seen only in thyroid antibody-positive individuals.…”
Section: Discussionsupporting
confidence: 91%
“…For this, we applied a population averaged procedure assuming a linear relationship between outcome and covariates, by use of population-averaged generalized estimating equations (PA-GEE) combined with a sandwich estimator (21). This approach accommodates repeated measurements without requiring a constant within-subject variation, and encompasses continuous non-normal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The presented results suggest beneficial effects of selenium on the autoimmune diseases of the TG [83,120]. In women at risk of postpartum thyroiditis, proper supplementation of the microelement may provide a prophylactic effect against the disease, although the data from clinical studies still require additional confirmation [121,122].…”
Section: Selenium In Autoimmune Diseases Of the Thyroid Glandmentioning
confidence: 80%
“…Opisane powyżej wyniki sugerują korzystny wpływ selenu na przebieg i występowanie autoimmunologicznych chorób tarczycy [83,120]. U kobiet zagrożonych wystąpieniem poporodowego zapalenia tarczycy właściwa podaż wspomnianego mikroelementu może zapobiegać tej jednostce chorobowej, choć dane płynące z badań klinicznych wymagają jeszcze dodatkowego potwierdzenia [121,122].…”
Section: Prace Poglądoweunclassified
“…However, one study showed significantly reduced postpartum thyroid dysfunction with the administration of Se 200 μg/day from midpregnancy onwards [10] . A double-blind, randomized, placebo-controlled study demonstrated that supplementation with Se 60 μg/ day in pregnant women with mild-to-moderate Se deficiency did not impact TPOAb concentration, but it did tend to alter thyroid function in TPOAb-positive women [19] .…”
Section: Pregnancymentioning
confidence: 99%